The association of chronotype, sleep duration and trajectories of health-risk behaviors among college students: a cohort study - Wanyu Che; Chenfang Wang; Shuman Tao; Tingting Li; Yang Xie; Fangbiao Tao; Xiaoyan Wu (Child and Adolescent Psychiatry and Mental Health)
Abstract Purpose To describe the trajectories of health-risk behaviors (HRBs) among college students through four consecutive surveys and explore the relationship between chronotype, sleep duration and different trajectories of HRBs. Methods We used a data sample of 1,042 college students from the College Student Behavior and Health Cohort Study. Students reported sleep parameters, including chronotype (Morningness-Eveningness Questionnaire-5, MEQ-5) and sleep duration. The behavior scale was used to evaluate four HRBs (smoking, alcohol use, low physical activity, smartphone addiction). The latent class growth analysis (LCGA) was used to estimate the trajectory of self-reported HRBs. Multivariate logistic regression models were used to study whether sleep parameters (chronotype and sleep duration) correlated with HRBs’ trajectories. Results Four unique trajectories of behaviors were identified: unhealthy group (7.4%), increasing group (21.3%), decreasing group (10.3%) and healthy group (61.0%). Compared with the normal sleep, results from logistic regression analyses indicated that long sleep (> 9 h) was associated with the decreasing group and the unhealthy group (P < 0.05), while short sleep (< 7 h) was associated with the increasing group and the unhealthy group (P < 0.05). Compared with the M-type, the E-type were positively correlated with the unhealthy group, the increasing group, and the decreasing group (P < 0.05). Conclusion E-type, short sleep duration and long sleep duration were significantly associated with the trajectory of HRBs. Findings underscore the need for targeted screening and prevention of modifiable sleep behaviors with the aim of improving HRBs in college students.